Recognition of Human Oncogenic Viruses by Host Pattern-Recognition Receptors - Di Paolo, Nelson C. (Frontiers in Immunology, 2014)
Human oncogenic viruses include Epstein-Barr virus (EBV), hepatitis B virus (HBV), hepatitis C virus (HCV), human papilloma virus (HPV), human T-cell lymphotropic virus (HTLV-1), Kaposi’s associated sarcoma virus (KSHV), and Merkel cell polyomavirus (MCPyV). It would be expected that during virus-host interaction, the immune system would recognize these pathogens and eliminate them. However, through evolution, these viruses have developed a number of strategies to avoid such an outcome and successfully establish chronic infections. The persistent nature of the infection caused by these viruses is associated with their oncogenic potential. In this article, we will review the latest information on the interaction between oncogenic viruses and the innate immune system of the host. In particular, we will summarize the available knowledge on the recognition by host pattern-recognition receptors (PRRs) of pathogen-associated molecular patterns (PAMPs) present in the incoming viral particle or generated during the virus’ life cycle. We will also review the data on the recognition of cell-derived danger associated molecular patterns (DAMPs) generated during the virus infection that may impact the outcome of the host-pathogen interaction and the development cancer.